Study on Effect of Aggregate Gradation on Geopolymer Semi-Flexible Pavement for Flexural Strength - Mohd Raffee, Muhammad Hidayat (IRC, 2019)
Formation of semi flexible pavement is focusing on a very open porous asphalt skeleton and using selected cementitious grout to fill in the voids.